Assessment of active spinal inflammatory changes in patients with axial spondyloarthritis: validation of whole body MRI against conventional MRI. Issue 4 (4th May 2009) - Weber, Ulrich; Hodler, Juerg; Jurik, Anne G; Pfirrmann, Christian W A; Rufibach, Kaspar; Kissling, Rudolf O; Khan, Muhammad A; Lambert, Robert G W; Maksymowych, Walter P
Abstract : Objective: To evaluate the performance of whole body (WB) MRI versus conventional (CON) MRI in assessing active inflammatory lesions of the entire spine in patients with established and clinically active axial spondyloarthritis (SpA) using the Spondyloarthritis Research Consortium of Canada (SPARCC) MRI index. Methods: 32 consecutive patients with SpA fulfilling the modified New York criteria and with clinically active disease (Bath Ankylosing Spondylitis Disease Activity Index (BASDAI) score ≥4) were scanned by sagittal WB and CON MRI of the spine. The MR images were scored independently in random order by three readers blinded to patient identifiers. Active inflammatory lesions of the spine were recorded on a web-based scoring form. Pearson correlation coefficients were used to compare scores for WB MRI and CON MRI for each rater and intraclass correlation coefficients (ICC) were used to assess interobserver reliability. Results: The median percentage of inflammatory lesions recorded concordantly for both WB MRI and CON MRI ranged from 83% to 91% for the three readers; 4–9% were only recorded by WB MRI and 4–9% were recorded by CON MRI only. The Pearson correlation coefficients between WB and CON MRI per rater were 0.79, 0.89 and 0.81, respectively. The ICC(2, 1) were 0.75, 0.80 and 0.68 for CON MRI and 0.82, 0.83 and 0.93 for WB MRI for the three possible reader pairs. Conclusion: WB MRI and CON MRI scores showed a high correlation and comparable high reliability for the detection of active inflammatory lesions in the spine of patients with clinically active SpA.